Le premier degré de la littérature : théorie littéraire et enseignement - Jérôme David (Cahiers de Narratologie)
The theory of a first degree of literature was conceived in the early 2010s to overcome many of the aporias of literary studies at the time. Nourished by a radical philosophy of imagination (inspired by the work of Castoriadis) and ontology (articulated to that of Quine), it aims to transform the critical gesture in its aim and methods. In this paper, we will detail the didactic transposition of some of its central concepts, and illustrate their impact on school micro-reading.